Supply chain resilience enhancement strategies in the context of supply disruptions, demand surges, and time sensitivity - Xin Yan; Jian Li; Yanan Sun; Robert De Souza (Fundamental Research)
Supply chain disruptions, including trade disputes, regional conflicts, and the COVID-19 pandemic, have highlighted the importance of supply chain resilience. This study focuses on investment decisions related to supply chain resilience, including considerations of supply disruptions, demand surges, and demand time sensitivity. The study uses a Stackelberg game model, with the retailer as the leader and the supplier as the follower, to analyze and compare optimal strategies for supply chain participants under different levels of risk. The results show that the severity of risk events impacts the optimal retail price, optimal wholesale price, supply chain recovery time, and expected profits for each participant. The investment in supply capacity enhancement not only expands the ability to meet demand but also encourages suppliers to expedite supply chain recovery, elevate demand fulfillment rates, and enhance the overall return on investment in supply chain resilience. As a result, the resilience of the entire supply chain is fortified. Similarly, it has been found that centralized decision-making leads to lower prices, shorter recovery times and greater supply chain resilience than decentralized decision-making. This study offers theoretical underpinning for corporations to effectively address risky occurrences, ensure supply security, enhance supply chain resilience, and imparts support for governments involved in humanitarian relief efforts.